2006
DOI: 10.1073/pnas.0601505103
|View full text |Cite
|
Sign up to set email alerts
|

Specificity in substrate and cofactor recognition by the N-terminal domain of the chaperone ClpX

Abstract: Clp ATPases are a unique group of ATP-dependent chaperones supporting targeted protein unfolding and degradation in concert with their respective proteases. ClpX is a representative member of these ATPases; it consists of two domains, a zinc-binding domain (ZBD) that forms dimers and a AAA ؉ ATP-binding domain that arranges into a hexamer. Analysis of the binding preferences of these two domains in ClpX revealed that both domains preferentially bind to hydrophobic residues but have different sequence preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 23 publications
(43 reference statements)
2
42
0
Order By: Relevance
“…Based on our data with E. coli proteins, we propose a possible explanation for the effect of ATP on ClpX activity to inhibit FtsZ assembly; ATP binding induces conformational changes of ClpX leading to unsuitable structures of the N-terminal domain of ClpX for binding to FtsZ. Actually, binding and/or hydrolysis of ATP in the AAA ϩ domain of ClpX induces a large movement of the N-terminal domain (34). Because the N-terminal domain of ClpX forms dimers (4) and has the ability to inhibit the FtsZ assembly, large oligomer formation in the presence ATP or stable hexamer formation in the presence of ATP␥S (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our data with E. coli proteins, we propose a possible explanation for the effect of ATP on ClpX activity to inhibit FtsZ assembly; ATP binding induces conformational changes of ClpX leading to unsuitable structures of the N-terminal domain of ClpX for binding to FtsZ. Actually, binding and/or hydrolysis of ATP in the AAA ϩ domain of ClpX induces a large movement of the N-terminal domain (34). Because the N-terminal domain of ClpX forms dimers (4) and has the ability to inhibit the FtsZ assembly, large oligomer formation in the presence ATP or stable hexamer formation in the presence of ATP␥S (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7), but other parts of FtsZ are also recognized by the N-terminal domain of ClpX. Previously, it has been reported that the N-terminal domain of ClpX preferentially recognizes several signal sequences containing hydrophobic residues (34). Based on their results, we searched for ClpX recognition signals in FtsZ and found several candidates (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent analysis of the binding properties of the ZBD using chemical shift perturbations showed that this domain employs mainly hydrophobic patches on its surface to recognize the substrate signal SspB2, enhancing the degradation efficiency by the ClpXP unfoldase/protease machinery [233,234]. Investigating the interaction of the ZBD with the O replication initiator protein revealed an overlapping binding site with the ClpX co-factor SspB2, highlighting the role of the ZBD in unfolding/degradation recognition [235].…”
Section: Clp Familymentioning
confidence: 99%
“…Similarly, a peptide from the kO substrate, which binds to the N domain of ClpX, contains an LLAI 56 sequence. 16 Moreover, the C-terminal residues of the phage MuA protein (LDILEQNRRKKAI 662 ) target it for ClpXP degradation in a partially N-domain-dependent manner and share homology with the Cc SspBa XB peptide. 12,18,35 Peptide-binding domains (PDZ, WW, SH2, SH3, PTB, FHA, 14-3-3, EVH1, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…However, ClpX DN fails to recognize certain substrates and does not support degradation mediated by many adaptors. 10,12,[14][15][16][17][18] SspB consists of a dimeric substrate-binding domain, followed by a flexible linker and a C-terminal peptide that binds to the ClpX N domain. 8,15,[19][20][21][22][23] By binding to ClpX and specific substrates, simultaneously, SspB increases the local concentration of substrate relative to the protease.…”
Section: Introductionmentioning
confidence: 99%